PENGARUH LIVE STREAMING SHOPPING DAN PRICE DISCOUNT TERHADAP PURCHASE INTENTION PADA APLIKASI TIKTOK (STUDI KASUS BRAND SKINCARE THE ORIGINOTE) - Pitaloka, Diah; Jaya, Umban Adi (Jurnal Pijar, 2024)
This research was conducted on consumers of The Originote in Sukabumi City. The purpose of this study was to determine the effect of live streaming shopping and price discounts on purchase intention.  This research uses quantitative methods, which means collecting data in the form of numbers. Researchers in this study conducted a survey using a questionnaire distributed to samples online. The population in this study are users of The Originote products and use the TikTok application as a means of online shopping in Sukabumi City. Which resulted in a sample of 100 respondents. In processing using SPSS 29 software with multiple linear analysis techniques which include validity tests, reliability tests, and classical assumption tests consisting of normality tests, multicolonearity tests, heteroscedasticity tests, then hypothesis testing consisting of t tests, f tests and determination coefficient tests. The effect of Live Streaming Shopping and Price Discount on Purchase Intention in the Tiktok application by taking a case study on the skincare brand The Originote shows that Live Streaming Shopping and Price Discount have a positive and significant influence on consumer Purchase Intention in the TikTok application.